2020
DOI: 10.1111/een.12928
|View full text |Cite
|
Sign up to set email alerts
|

Plant water stress intensity mediates aphid host choice and feeding behaviour

Abstract: 1. The effects of drought-induced changes in plant quality on aphid performance and population growth is well-studied. The response of aphid behaviour to plant water limitation has received less attention. Water limitation may affect host-plant colonization by altering the attractiveness of plants. Additionally, plant water limitation may inhibit feeding site establishment and phloem ingestion. 2. Our goal was to examine bird cherry-oat aphid (Rhopalosiphum padi L.) host selection and feeding behaviour under w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Although many studies have reported reduced aphid fitness when exposed to drought‐stressed hosts (Banfield‐Zanin & Leather, 2015 ; Dai et al., 2015 ; Foote et al., 2017 ; Kansman et al., 2020 ), studies have reported null (Mewis et al., 2012 ) and positive (Oswald & Brewer, 1997 ) effects. Multiple factors could explain these contrasting observations, including differences in aphid or plant biology.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have reported reduced aphid fitness when exposed to drought‐stressed hosts (Banfield‐Zanin & Leather, 2015 ; Dai et al., 2015 ; Foote et al., 2017 ; Kansman et al., 2020 ), studies have reported null (Mewis et al., 2012 ) and positive (Oswald & Brewer, 1997 ) effects. Multiple factors could explain these contrasting observations, including differences in aphid or plant biology.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent meta-analysis encompassing 55 published studies on the effect of drought on sap-feeding insects, showed that, for Poaceae (n = 24 studies), aphid tness is generally reduced under low soil moisture conditions (Leybourne et al 2021). For example, the tness of the foliage aphid Rhopalosiphum padi L. was reduced when feeding on drought-stressed wheat (Triticum aestivum L.) (Kansman et al 2020). Multiple factors could explain the variation between these studies including aphid and/or host biology.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with bugs native to the ants' introduced range may also be important for facilitating invasion [37]. Honeydew producers may benefit from intermittent drought due to increased nitrogen availability in phloem [48], which may reduce honeydew excreted per individual [49]. Elevated carbon dioxide and/or temperature affect population growth, behaviour, honeydew production, and chemical communication of sap-sucking insects sometimes to the benefit of the ants or their trophobionts, but often dependent on host plants, seasonal timing, ant attendance, or natural enemies [7, [50][51][52][53][54].…”
Section: Acquiring Plant-based Carbohydrate Resourcesmentioning
confidence: 99%